Surface ultrastructure of silicone rubber aortic valve poppetts after long-term implantation. A scanning electron microscope study of four poppets. Issue 6 (December 1976) - Allwork, S P; Norton, R
Abstract : The surface ultrastructure, demonstrated by scanning electron microscopy, is described in four implanted Silastic aortic valve poppets. Ball variance was discovered at necropsy in two patients and clinically in one in whom the poppet was replaced. The fourth patient underwent reoperation, but ball variance was neither suspected nor found. All four poppets were densely coated with biological debris and microthrombi. The 'coat' was soluble in a weak solution of sodium hydroxide. The true Silastic surface beneath the coat was little altered compared with unimplanted poppets, even after 10 years' implantation.